Glycopolymer-Wrapped Carbon Nanotubes Show Distinct Interaction of Carbohydrates With Lectins - DiLillo, Ana M.; Chan, Ka Keung; Sun, Xue-Long; Ao, Geyou (Frontiers in Chemistry, 2022)
Glyconanomaterials with unique nanoscale property and carbohydrate functionality show vast potential in biological and biomedical applications. We investigated the interactions of noncovalent complexes of single-wall carbon nanotubes that are wrapped by disaccharide lactose-containing glycopolymers with the specific carbohydrate-binding proteins. The terminal galactose (Gal) of glycopolymers binds to the specific lectin as expected. Interestingly, an increased aggregation of nanotubes was also observed when interacting with a glucose (Glc) specific lectin, likely due to the removal of Glc groups from the surface of nanotubes resulting from the potential binding of the lectin to the Glc in the glycopolymers. This result indicates that the wrapping conformation of glycopolymers on the surface of nanotubes potentially allows improved accessibility of the Glc for specific lectins. Furthermore, it shows that the interaction between Glc groups in the glycopolymers and nanotubes play a key role in stabilizing the nanocomplexes. Overall, our results demonstrate that nanostructures can enable conformation-dependent interactions of glycopolymers and proteins and can potentially lead to the creation of versatile optical sensors for detecting carbohydrate-protein interactions with enhanced specificity and sensitivity.